(untitled) (Veterinary Science, 2024)
Wolves have been always admired by humans, beyond the evolutive nearness to domestic dogs, his veterinarian management is something different due to their savage nature. The objective of this work is to offer information about the clinical approach to diseases of animals in captivity, their management, and resolution. An old male of 14 years old European Wolf (Canis lupus) coming from a loan, evidenced in acute form fly eggs at the tail base, appetite loss, and pruritus, a chemical contention was performed to make a proper clinical examination, showing myiasis, and multiple epidermic nodules infection at loin and rump. We decided to go through the anesthesia procedure and solve the nodules by surgery , then send it for histopathology